The Predictive Factors of Mortality In COVID-19 In The Intensive Care Unit: A Retrospective Study From Universitas Airlangga Hospital Surabaya - Wennas, Vindy Vanessa; Bakhtiar, Arief; Yusuf, Mochamad; Effendi, Wiwin Is (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2025)
Background: Coronavirus disease 2019 (COVID-19) poses a significant global challenge due to its highly transmissible nature and many positive cases and deaths. Myriad factors are known to affect the outcome of COVID-19 patients. Therefore, identifying predictive factors is essential for developing strategies to reduce mortality. Methods: An analytical observational retrospective study was conducted at Universitas Airlangga Hospital Surabaya from January to June 2021. A total of consecutive sampling was performed on all patients in the intensive care unit. Thirty-one variables were included and analysed using a two-step statistical analysis: univariate and multivariate logistic regression. Results: The mortality rate among 116 patients was 61.2%. The univariate analysis showed that dyspnoea, hypoxia, hyperglycaemia, and fever at admission were positively correlated with mortality. The multivariate analysis showed that fever (adjusted odds ratio [OR]=5) and hyperglycaemia (adjusted OR=8) at admission were independent predictors of mortality. Conclusion: Patients with hyperglycaemia or fever at admission face an increased likelihood of dying from COVID-19, with risks elevated by eight times and five times, respectively.